An Early Devonian clam shrimp community from Hunan Province, China. (January 2022) - Liao, Huanyu; Shen, Yanbin
Abstract: The Devonian saw the emergence and subsequent diversification of the clam shrimp. To date, there are no credible records of any clam shrimp prior to the Devonian. Therefore, discoveries and taxonomic studies of early forms, especially the Early Devonian species, are essential to broaden our knowledge of the origin and early evolution of clam shrimp. An Early Devonian clam shrimp community that consists of four species, Cornia cheni n. sp., Pseudestheria cf. P . diensti, Palaeolimnadiopsis zhangi n. sp., and ? Palaeolimnadia sp. is described and discussed in detail in this study. These species are the oldest clam shrimp in China and among the oldest worldwide. This discovery indicates that clam shrimp communities with high diversity existed since the late Early Devonian and that their early forms may have had a profound effect on the origin and evolutionary trends of the following forms. UUID: http://zoobank.org/ae9d0ab8-0b0e-4103-ad71-601d11a024fc .